INCLUDING STUDENTS OF HUMANITARIAN IDEAS IN PRIMARY EDUCATION (Archive of Conferences, 2022)
In the world humanity ignorant from the man madad wait, your life zoye transfer. Abdulqodir Bedil. Humanity is human dignity, freedom, happiness, equality legitimacy about humanity all principles to the surface remove for condition - conditions creating give about care to do representative understanding. Unga according to the world eng valuable thing is human, whole being, being to man, his happiness - bliss service do should. Human destiny, people interests, country people about care of humanity basic is a matter. Humanity ideas long to date has They are happiness and to justice achieve dreams of in the style of from ancient times people orally in creativity, in literature , in religion and philosophical in the teachings own aksini find is coming.